Sentencing Drug Court Failures: Judicial Considerations With Increased Offender Information. (March 2020) - Gibbs, Benjamin R.
This study explores the influential predictors of sentence severity within a sample of drug court failures. This sample is unique, in that, judges possess greater amounts of offender information at the time of sentencing, relative to conventional adjudications. Due to defendants' participation in a drug court program, judges possessed offender program performance information in addition to traditionally assessed criminogenic and offender indicators. Data were collected from 320 individuals who participated, yet failed, in Midwestern adult felony drug court program. Results suggest that, in these instances, judicial sentencing decisions were influenced by case and program performance characteristics. Moreover, judges who oversaw defendants in the program sentenced participant failures more harshly than judges who had no affiliation with the drug court or offender prior to sentencing.